Do halal certification and cruelty-free labeling affect purchase decisions for local cosmetic products? - Atika Zahra; Nurul Hidayati; Mohd. Firdaus Ruslan (Halal Studies and Society, 2026)
Indonesian local cosmetic industry is expanding, driven by increasing consumer awareness of product quality, ethical considerations, and sustainability. The expansion further compels firms to adapt their marketing strategies to meet increasingly discerning consumer preferences. Therefore, this study aimed to examine the influence of halal certification and cruelty-free labeling on purchase decisions in Jakarta Special Capital Region (DKI Jakarta). Data were obtained through a questionnaire administered to 200 respondents who had purchased halal-certified and cruelty-free cosmetic products in the preceding 3 months. The survey was conducted between October 2024 and December 2025. A non-probability method using purposive sampling was adopted in selecting respondents. Data analysis comprised descriptive statistics, validity and reliability tests, and Structural Equation Modeling–Partial Least Squares (SEM-PLS), facilitated by SPSS 26 and SmartPLS 4. The results showed that the majority of respondents were young adult women. Additionally, both halal certification and cruelty-free labeling were found to have positive and statistically significant influence on purchase decisions with p-values less than alpha=0.05.